Experimental Dynamic Testing and Numerical Modeling of Historical Belfry. Issue 4 (18th May 2016) - Nisticò, N.; Gambarelli, S.; Fascetti, A.; Quaranta, G.
ABSTRACT: The experimental characterization of historical bell towers and wall belfries can provide important information for the calibration of numerical models as well as to implement proper restoration strategies. Within this framework, the presented study is concerned with the experimental dynamic assessment of an ancient belfry dating back to 1537. The structure is part of the "Santa Maria in Aracoeli Church" (Rome, Italy), an important heritage construction placed on the summit of the Capitoline Hill, close to the building that hosts the Major's office. Several field tests have been conducted using accelerometers, and records obtained under different dynamic loading scenarios have been examined. Moreover, experimental accelerations have been elaborated to estimate the most important modal features of the structure and to validate a finite element model. Field tests have confirmed that severe vibrations are induced when the bells swing, and thus a slight reduction of the swing angle has been suggested in order to provide an immediate and inexpensive benefit to the structure. A new set of field tests demonstrates that the new swing angle is sufficient to reduce the induced vibrations while preserving the original sound.